Carlo Antici e l'ideologia della Restaurazione in Italia - Pestelli, Corrado (Studi e saggi, 2009)
Carlo Antici e l'ideologia della Restaurazione in Italia traces Antici's career as an essayist, translator of works of the Catholic Restoration and contributor to journals. This appraisal brings to light the link (albeit not designatory) with the ideology of conservative romanticism, as witnessed by the citations from Chateaubriand, the early Lamennais and De Maistre. Penned in the form of utopian essay, Antici's standpoint tends towards a theocratic concept and a renewed patrimonialist vision of the State, surfacing in the hope of an Empire-Papacy combination. The relationship with Giacomo Leopardi in its turn triggers a series of suggestions for reading destined to be independently reworked by a nephew anything but deaf to dialogue with his uncle, readings that range from the ancients, especially Greek, to the aforementioned contemporary French Catholic writers.